Improving Adolescent HIV/AIDS Knowledge through Video-Based Health Education: A School-Based Study in Indonesia - Yulia Intan Fatriana; Dhesi Ari Astuti (The Indonesian Institute of Science and Technology Research, 2026)
HIV/AIDS remains a significant global and national public health problem every year. Adolescents are a group highly vulnerable to HIV/AIDS transmission because of the transitional phase marked by high curiosity, which leads them to seek information from various sources that are not necessarily accurate. This study aimed to determine the effect of health education using video media about HIV/AIDS on adolescent knowledge at SMP Negeri 1 Godean. This study was a pre-experimental study with a one-group pretest-posttest design. The sample consisted of 128 respondents selected using a total sampling technique. The data collection instrument used was a questionnaire. The data collection tool used was a questionnaire. Following the health education session using video media, respondents' knowledge levels showed a marked increase, with 127 respondents (99.22%) in the good category and 1 respondent (0.78%) in the fair category. The results of the Wilcoxon statistical test showed a p-value of 0.00, Z = -9.822 for knowledge. A statistically significant increase in adolescent knowledge was found following health education using video media on HIV/AIDS at SMP Negeri 1 Godean, Yogyakarta. Respondents are expected to maintain this knowledge to avoid deviant behavior and increase concern for people living with HIV/AIDS (PLWHA).